ANALISIS EFISIENSI LEMBAGA PENGELOLA ZAKAT (LPZ) DALAM MENGELOLA POTENSI ZAKAT DI INDONESIA - M Sofian Anwar; Itang Itang; Havid Risyanto (Tazkiya, 2019)
About the potential of zakat Muslims were quite large and increasing every year, but the absorption of the potential zakat which are associated are still minimal caused community awareness of the knowledge zakat and confidence in the management of zakat management institutions .This mengindikasi that their level of efficiency of zakat management institution performance (LPZ) has not yet been optimized. This research aims: first to analyze the efficiency rate of the Board of Zakat Management (LPZ) in managing the potential of zakat in Indonesia using a method of non parametric data Envelopment analysis (DEA) in the year 2015-2017. Second to analyze the average efficiency of the Zakat Management Institute (LPZ) in managing the potential of zakat in Indonesia using a method of non parametric data Envelopment analysis (DEA) in the year 2015-2017. The results of the five-scale LPZ efficiency analysis in Indonesia using the Data Envelopment Analysis (DEA) method assuming that the Variable Return To Scale (VRS)-oriented technical Output in the period of 2015-2017 showed that the average efficiency LAZ Rumah Zakat is in the efficiency of approaching the perfect efficiency of 94.58% and two other LPZ LAZ Al Azhar 84.02% and BAZNAS 88.21 are in sufficient efficiency, followed by LAZ Rumah Yatim Arrohman with an average value of efficiency 64.63 %. While LAZ Yayasan Dana Sosial Al Falah is in the lowest efficiency with an average value of 38.25 efficiency. In this case, it can be interpreted that LPZ in Indonesia has not optimally managed all of its resources and has not been said to be efficient in the output of outputs in the observation period.